Análisis temporal y espacial de los indicadores de siniestralidad vial en la ciudad de Bogotá D.C. (2023)
This study analyzes road accidents in the city of Bogotá between 2015 and 2021. The objective is to identify the evolution of accident indicators in order to make decisions to improve road safety. Secondary data was used, and a geospatial database was structured and refined to analyze the location, severity, and year of accidents.